2019
DOI: 10.1177/2050640619880362
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic measurement of gastric pH is associated with persistent acid reflux in patients treated with proton pump inhibitors for gastroesophageal reflux disease

Abstract: Background Proton-pump inhibitors (PPIs) are the mainstay of gastroesophageal reflux disease (GERD) treatment, however, up to 30% of patients have a poor symptomatic response. PH-impedance is the gold standard to assess whether this is due to persistent acid reflux. We aimed to characterize clinical predictors of persistent esophageal acid reflux on PPIs including gastric pH measured during endoscopy. Methods We prospectively recruited patients with GERD and/or Barrett’s esophagus (BE) on PPIs. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Drugs of choice for GERD pharmacotherapy are antisecretory agents and primarily proton pump inhibitors (PPIs) (Sawada, 2020;Sharma, Yadlapati, 2020;Surdea-Blaga, 2016). Two ways can also be used to increase the effectiveness of treatment and the rapid elimination of symptoms, including the combination of PPIs with alginates, antacids, or prokinetics or increasing the dose of the drug (Januszewicz, 2019). The expediency of the use of pharmaceuticals aimed at protecting the mucous membrane of the esophagus is due to the pathogenesis of GERD, namely -cellular and molecular mechanisms of inflammatory changes in the mucous membrane of the esophagus.…”
Section: Resultsmentioning
confidence: 99%
“…Drugs of choice for GERD pharmacotherapy are antisecretory agents and primarily proton pump inhibitors (PPIs) (Sawada, 2020;Sharma, Yadlapati, 2020;Surdea-Blaga, 2016). Two ways can also be used to increase the effectiveness of treatment and the rapid elimination of symptoms, including the combination of PPIs with alginates, antacids, or prokinetics or increasing the dose of the drug (Januszewicz, 2019). The expediency of the use of pharmaceuticals aimed at protecting the mucous membrane of the esophagus is due to the pathogenesis of GERD, namely -cellular and molecular mechanisms of inflammatory changes in the mucous membrane of the esophagus.…”
Section: Resultsmentioning
confidence: 99%
“…A real‐time measure of the pH during endoscopy was able to provide, on 122 prospectively enrolled patients, a good correlation with the 24‐h esophageal acid exposure time on pH impedance 1 …”
Section: Endoscopymentioning
confidence: 99%
“…A real-time measure of the pH during endoscopy was able to provide, on 122 prospectively enrolled patients, a good correlation with the 24-h esophageal acid exposure time on pH impedance. 1 Still related to the esophagus (and also stomach), the use of probe-based confocal laser endomicroscopy (p-CLE) on 74 lesions was investigated, with p-CLE providing overall diagnostic accuracy for malignant lesions of 89%, versus biopsies with 85% of accuracy. 2 The advent of new devices in the endoscopy field was also highlighted in a study on the use of Hemospray where a single-arm, prospective multicenter study on 73 patients reported a rate of immediate hemostasis achieved in 100%, with only 4% of patients suffering from re-bleeding and no adverse events due to the use of Hemospray.…”
Section: Endoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time monitoring of intragastric pH after PPI administration using a pH monitor may be a valuable tool for investigators comparing PD parameters between study drugs. 17,18 The intragastric pH level was automatically and continuously recorded by a pH monitor (Ohmega R; Enschede, The Kingdom of the Netherlands) and MMS Database software. A flexible, single-use, single-channel antimony pH catheter (ZandorpH Laborie; Enschede, The Kingdom of the Netherlands) was introduced through the nasopharynx to reach the stomach.…”
Section: Intragastric Ph Monitoringmentioning
confidence: 99%